ANALISIS KONSUMSI BAHAN BAKAR MESIN PEMOTONG RUMPUT MENGGUNAKAN REMOTE CONTROL - Indrawan, Baeni (Politeknik Harapan Bersama Tegal, 2023)
Abstract – A lawan mower is a tool used for cutting grass or plants. This tool is ususally used to tidy up the garden. One of the most important suppliers of lawn mowers using remote control is fuel so that the lawn mower can move according to is permormance. The purpose of this final project is to find out how the fuel consumption of a lawn mower uses a remote control. The test was carried out ussing a lawn mower with a capacity of 196cc which was operated at speeds of 1500, 2000 and 2500rpm. The fuel used is pertalite and pertamax 92. The test results show that the higher the engine speed, the greater the cutting capacity. High fuel flow rate (consumption) with engine speed, it is very important to analyze the fuel consumption with the results of 5,7 ml/seconds at 1500rpm rotation, at 2000rpm 6,8 ml/second using pertalite fuel and at 2500rpm rotation 9,5 ml/second results. At 1500rpm, 2000rpm and 2500rpm engine speed using pertamax fuel is 6,2 ml/second, 9,3 ml/second and 9,3 ml/second.